Being a Candidate for Special Talented Identity: Assessment of Parents' to the Student Identification Process Through Domestic Psychosocial Experiences - Pınar Özdemir-Kemahlı; Şevket B. Kemahlı; Halil Ekşi (Anı Publishing, 2018)
This research was conducted for the purpose of examine the perception of the parents of children who participated in the BİLSEM student identification process after nominated to receive as special talented by their schools. It is also aimed to evaluate their views on the family psycho-social experiences during the identification process. In the research, interpretative phenomenological design as one of the qualitative research patterns was utilized. Eighteen families participated in the research during the period of group screenings of 2016-2017 academic year, BİLSEM student identification process. In the study, data were gathered through semi-structured interview form and interpretative phenomenological analysis method was used in data analysis. For the parents, the child's nomination for the identification process was considered to be different from his peers, successful in the name of himself and his child as well as high expectation in education and anxiety about not receiving identity. It can be said that participation in the student identification process has caused changes in many functions related to the family environment. Taking these findings into consideration, it is necessary for parents to be conscious about the fact that the child is a candidate for the student recognition process and that it is understood in accordance with the application and the literature. It is also recommended that protector/preventive counseling services be provided to all family members regarding the effects on the family.